MANAGING CHANGE: THE PRIVATE UNIVERSITY SECTOR IN CYPRUS, OPERATIONS WITHIN THE EUROPEAN CONTEXT. A CASE STUDY - SIMONA MIHAI YIANNAKI (Challenges of the Knowledge Society)
Our case study attempts to show the manner by which change has been introduced and dealt within the Business School of a private Cypriot University, the European University Cyprus. Then it tries to demonstrate if the success of the change process has its roots in the history of the organization and its representative strategies as per the theoretical framework of the literature review. Out of the main study results it emerges that it is the trust placed on the organization by the management, the staff and the student body that can bring high standards of education to the change process along with the acceptance for process and embedded innovation. At the other end, there are still strong drawbacks that hider change management to its full positive results. These reside mostly the inequalities, the social contract issues and keeping promises.